EFFECTIVENESS OF PT. ABC EMPLOYEE TRAINING PROGRAM - Krisna Primastya; Heru Baskoro (STMIK Indonesia Banda Aceh, 2026)
This study aims to identify the factors contributing to the failure of the employee training program at PT. ABC in achieving its annual targets and to evaluate the program's effectiveness in enhancing employee skills. The research employs a qualitative approach, utilizing interviews and document analysis as data collection techniques. The findings reveal that the program's failure is due to the lack of relevance between the training content and the company's operational needs, as well as limitations in the delivery methods used. Additionally, suboptimal training management contributes to the low effectiveness of the program. The study concludes that the program's effectiveness remains low because the training materials are not integrated with employees' specific job requirements. The study's limitation lies in its focus on a single company without comparisons to other organizations. The implications of this research highlight the need for improvements in the training curriculum, delivery methods, and training management systems to ensure greater relevance and effectiveness in enhancing employee performance.